Evidence-based recommendations for induction and maintenance treatment of newly diagnosed transplant-ineligible multiple myeloma patients. (August 2022) - Rafae, Abdul; Ehsan, Hamid; Wahab, Ahsan; Khan, Sana Irfan; Khan, Israr; Ashraf, Sara; Ali, Sundas; Khalid, Farhan; Neupane, Karun; Valent, Jason; Khouri, Jack; Samaras, Christy; et al.
Abstract: There is increasing evidence regarding the role of various maintenance therapy (MT) strategies after initial induction to treat newly diagnosed transplant-ineligible patients with MM. We reviewed the literature on available regimens for patients with transplant-ineligible newly diagnosed multiple myeloma (NDMM). Lenalidomide (R)-based regimens are still the front-line therapy, but there is an increasing use of bortezomib-based regimens. The MT regimen is mainly based on the initial induction regimen. MT has shown survival benefits compared with patients without maintenance therapy. The most common adverse effects of MT include anemia, neutropenia, thrombocytopenia, infections, and peripheral neuropathy. In conclusion, induction followed by maintenance based on lenalidomide, bortezomib, ixazomib, or daratumumab-based regimens has shown promising results. Therefore, it is essential to conduct more clinical trials to better understand the role of MT in the treatment of NDMM patients who are not candidates for autologous stem cell transplantation. Highlights: Maintenance therapy following induction improves survival in TI-NDMM patients. Four drug regimens have better outcomes and good MRD negative rate. D -Rd is superior to continuous Rd therapy in terms of durability of response and survival. Peripheral neuropathy associated with bortezomib-based regimens limits their use. Ixazomib based regimes have good efficacy in elderly TI-NDMM patients.